Real-time protection and monitoring of three phase induction motor using arduino - Masely, Fahrul; Tri Putra Yanto, Doni; Yelfianhar, Ichwan; Elvanny Myori, Dwiprima (Journal of Industrial Automation and Electrical Engineering, 2024)
Electric motor protection in modern industry is increasingly important along with technological developments and the need to maintain operational reliability and prevent unwanted disturbances. This research develops an Arduino Mega-based three-phase induction motor protection system that uses PZEM-004T sensors to monitor current and voltage, and MAX6675 sensors to accurately measure motor temperature. The monitoring data is displayed in real-time on the ILI9341 TFT LCD screen, enabling early detection of abnormal conditions such as overheat, over current, and voltage imbalance. The system provides a quick response to protect motors from potential damage, ultimately preventing significant losses and ensuring operational continuity and energy efficiency in increasingly complex industrial environments